Assisted reproductive technologies and legal aspects of sex selection - S. Sh. Khayat (Andrologiâ i Genitalʹnaâ Hirurgiâ, 2019)
The paper covers the legal and ethical aspects of sex selection, and the dynamics of public opinion on this issue in different countries and regions of the world. Also, the results of two questionnaires, organized by Research Centre for Medical Genetics (2000 and 2017), are analyzed.